High-frequency gain enhancement of a broadband metasurface antenna with parasitic patches using characteristic mode analysis - Liu, Hailong; Yang, Zi; Gao, Yan; Dong, Lijuan; Guo, Yaru; Xu, Xin; Meng, Tianhua; Hu, Weidong; Feng, Caixia (Frontiers in Physics, 2025)
This paper presents a broadband metasurface (MTS) antenna using the characteristic mode analysis (CMA) method for high-frequency gain enhancement. First, by loading four parasitic patches around the 3 × 3 squared patches on the upper layer, the potential bandwidth of the characteristic modes of the MTS is broadened, and the impedance matching of the antenna is improved. As a result, the bandwidth of the proposed antenna is improved. However, the high-frequency realized gain of the antenna is significantly lower than that at low frequency because the mode at the high operating band has radiation null in the boresight direction. To address this, two slots along the x-axis are introduced in part of the unit cells of the MTS, according to the CMA, for mode optimization. The optimized higher-order modes (HOMs) then exhibit broadside radiation patterns at high frequency, leading to a significant improvement in high-frequency realized gain. Specifically, the realized gain at 7 GHz in the boresight direction is enhanced from −1.17 dBi to 9.5 dBi. The simulated and experimental results show that the proposed antenna achieves a 55.2% (4.66 GHz–8.22 GHz) impedance bandwidth for |S11| ≤ −10 dB, with a very flat gain of 7–10 dBi.